Enhancement of MCF-7 and HeLa cell interfacial interactions using pulse electric field and natural sustainable resources - Ganeson, Suhassni; Abdul Jamil, Muhammad Mahadi; Ambar, Radzi; Wan Zaki, Wan Suhaimizan; Abd Wahab, Mohd Helmy; Marimuthu, Shamala; Abd Rahman, Nur Adilah; Mamman, Hassan Buhari (2023)
Electroporation plays a part in chemotherapy, providing a promising strategy to increase the potency of anticancer medications and enhance treatment outcomes in some types of malignancies. Electroporation is a biological technique in which short electrical impulses are applied to cells or tissues, which temporarily destroying their cell membranes. This disruption creates temporary pores or channels in the cell membrane, allowing for the introduction of membrane that allow foreign substances such as DNA, RNA, proteins, proteins, or drugs into to enter the cells. The effectiveness of the technique will aid in the development of new cancer cell therapies and wound healing approaches. This review addresses the effects of electroporation techniques on breast cancer cells (MCF-7) and cervical cancer cell (Hela) using electric pulse ranging from 100-100V/cm. On top of that, honey extracts will be injected into breast cancer cells and cervical cancer cells using electrical pulses or the electroporation technique to examine the anti-cancer mechanism. This research finding may lead to fewer adverse effects of cancer treatment while maintaining patients' health and enhancing overall life expectancy.© 2024 The Authors. Published by ELSEVIER B.V. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0) Peer-review under responsibility of the scientific committee of the International Symposium on Green Technologies and Applications Keywords: Electroporation;MCF-7; Hela cell;Tualang honey;Kelulut honey Muhammad Mahadi bin Abdul Jamil. Tel.: +600167179179 Available online at www.sciencedirect.com ScienceDirect Procedia Computer Science 00 (2023) 000–000 www.elsevier.com/locate/procedia 1877-0509 © 2024 The Authors. Published by ELSEVIER B.V. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0) Peer-review under responsibility of the scientific committee of the International Symposium on Green Technologies and Applications International Symposium on Green Technologies and Applications (ISGTA’2023) Enhancement of MCF-7 and HeLa Cell Interfacial Interactions using Pulse Electric Field and Natural Sustainable Resources Suhassni Ganesona , Muhammad Mahadi bin Abdul Jamilb , Radzi bin Ambarc , Wan Suhaimizan bin Wan Zakid , Mohd Helmy Abd Wahabe ,Shamala Marimuthuf , Nur Adilah Abd Rahmang , Hassan Buhari Mammanh a,b,c,d,e,gUniversiti Tun Hussein Onn Malaysia, Biomedical Modelling and Simulation Research Group, Faculty of Electrical and Electronic Engineering, Batu Pahat 86400, Malaysia a,f Mila University, No. 1, Jalan MIU Boulevard, Nilai Putra, Nilai Seremban,71800, Malaysia h Tafawa Balewa University Bauchi Department of Electrical and Electronics Engineering, Nigeria Abstract Electroporation plays a part in chemotherapy, providing a promising strategy to increase the potency of anticancer medications and enhance treatment outcomes in some types of malignancies. Electroporation is a biological technique in which short electrical impulses are applied to cells or tissues, which temporarily destroying their cell membranes. This disruption creates temporary pores or channels in the cell membrane, allowing for the introduction of membrane that allow foreign substances such as DNA, RNA, proteins, proteins, or drugs into to enter the cells. The effectiveness of the technique will aid in the development of new cancer cell therapies and wound healing approaches. This review addresses the effects of electroporation techniques on breast cancer cells (MCF-7) and cervical cancer cell (Hela) using electric pulse ranging from 100-100V/cm. On top of that, honey extracts will be injected into breast cancer cells and cervical cancer cells using electrical pulses or the electroporation technique to examine the anti-cancer mechanism. This research finding may lead to fewer adverse effects of cancer treatment while maintaining patients' health and enhancing overall life expectancy.